2008
DOI: 10.1055/s-0028-1083500
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient One-Pot Synthetic Method for 2,4-Disubstituted 7-Arylpyrido[4,3-d]pyrimidines from 2,4-Disubstituted 6-(Arylethynyl)pyrimidine-5-carbaldehydes and tert-Butylamine

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In our previous report 8 we have shown that the cyclization of 2,4-disubstituted 6-arylethynylpyrimidine-5-carbaldehydes 2 with tert-butylamine proceeded via N-(tert-butyl)-N-{4-[(Z)-2-aryl-2-(tert-butylamino)vinyl]pyrimidin-5-yl}methyleneamines 4. The possible mechanism is presented in Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous report 8 we have shown that the cyclization of 2,4-disubstituted 6-arylethynylpyrimidine-5-carbaldehydes 2 with tert-butylamine proceeded via N-(tert-butyl)-N-{4-[(Z)-2-aryl-2-(tert-butylamino)vinyl]pyrimidin-5-yl}methyleneamines 4. The possible mechanism is presented in Scheme 4.…”
Section: Resultsmentioning
confidence: 99%
“…After heating, the solution was cooled to room temperature, then cold water (10 mL) was added. The precipitate was filtered, dried, and recrystallized to give 5a-t. 8, 14.2, 27.9, 109.3, 115.3, 127.1, 128.8, 129.5, 138.4, 149.6, 157.2, 157.5, 160.8, 171.8 8,66.6,108.9,115.4,127.2,128.9,129.6,138.2,149.5,157.1,157.7,161.9,165.2 ppm. Anal.…”
Section: -Amino-2-methylthio-6-(4-ethylphenyl)ethynylpyrimidine-5-camentioning
confidence: 98%
See 2 more Smart Citations